FUS-DDIT3 fusion protein-driven IGF-IR signaling is a therapeutic target in myxoid liposarcoma - Trautmann, Marcel; Fröhling, Stefan (Clinical cancer research, 2017)
Purpose: Myxoid liposarcoma is an aggressive disease with particular propensity to develop hematogenic metastases. Over 90% of myxoid liposarcoma are characterized by a reciprocal t(12;16)(q13;p11) translocation. The resulting chimeric FUS-DDIT3 fusion protein plays a crucial role in myxoid liposarcoma pathogenesis; however, its specific impact on oncogenic signaling pathways remains to be substantiated. We here investigate the functional role of FUS-DDIT3 in IGF-IR/PI3K/Akt signaling driving myxoid liposarcoma pathogenesis. Experimental Design: Immunohistochemical evaluation of key effectors of the IGF-IR/PI3K/Akt signaling axis was performed in a comprehensive cohort of myxoid liposarcoma specimens. FUS-DDIT3 dependency and biological function of the IGF-IR/PI3K/Akt signaling cascade were analyzed using a HT1080 fibrosarcoma-based myxoid liposarcoma tumor model and multiple tumor-derived myxoid liposarcoma cell lines. An established myxoid liposarcoma avian chorioallantoic membrane model was used for in vivo confirmation of the preclinical in vitro results. Results: A comprehensive subset of myxoid liposarcoma specimens showed elevated expression and phosphorylation levels of various IGF-IR/PI3K/Akt signaling effectors. In HT1080 fibrosarcoma cells, overexpression of FUS-DDIT3 induced aberrant IGF-IR/PI3K/Akt pathway activity, which was dependent on transcriptional induction of the IGF2 gene. Conversely, RNAi-mediated FUS-DDIT3 knockdown in myxoid liposarcoma cells led to an inactivation of IGF-IR/PI3K/Akt signaling associated with diminished IGF2 mRNA expression. Treatment of myxoid liposarcoma cell lines with several IGF-IR inhibitors resulted in significant growth inhibition in vitro and in vivo. Conclusions: Our preclinical study substantiates the fundamental role of the IGF-IR/PI3K/Akt signaling pathway in myxoid liposarcoma pathogenesis and provides a mechanism-based rationale for molecular- targeted approaches in myxoid liposarcoma cancer therapy.